Case report: Primary hyperparathyroidism due to mediastinal parathyroid adenoma - Milosheska, Radmila; Mickovski, Ivana; Crcareva, Biljana; Buklioska Ilievska, Daniela; Bundovska Kocev, Smiljana (Nizameddin KOCA, 2022)
Primary hyperparathyroidism is defined by elevated parathyroid hormone and calcium levels, most usually caused by a parathyroid adenoma. Parathyroid adenomas are most commonly detected in the neck or an ectopic site, seldom in the mediastinum. The parathyroid adenoma can occur in ectopic locations such as the mediastinum, thymus, or retro oesophagal area in 6-16% of cases. We presented the example of a 73-year-old woman who was found to have hypercalcemia during a regular test. The patient’s serum calcium (3.11 mmol/L), alkaline phosphatase (162 U/L), parathyroid hormone (PTH: 379 pg/mL) and creatinine (111.6 umol/L) levels were higher than the reference values. A chest computerized tomography scan revealed an anterior mediastinal mass, and nuclear scintigraphy revealed functioning parathyroid tissue in the mediastinum. The mediastinal parathyroid adenoma was effectively removed surgically, and the PTH level began to fall. Any hypercalcemia and high PTH levels in the absence of a parathyroid adenoma in the neck should prompt clinicians to look for ectopic sites using a mix of imaging modalities.
Keywords: Primary hyperparathyroidism; scintigraphy